How reliable are case formulations?: a systematic literature review - Flinn, Lucinda; Braham, Louise; das Nair, Roshan (Wiley, 2015)
Objectives: This systematic literature review investigated the inter-rater and test–retest reliability of case formulations. We considered the reliability of case formulations across a range of theoretical modalities and the general quality of the primary research studies.